2009
DOI: 10.1007/s11947-009-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Time of Entry of Salmonella and Campylobacter into the Turkey Brooder House

Abstract: The prevalence of Campylobacter (>90%) and Salmonella (33%) in turkeys at slaughter has been estimated. This report describes studies to estimate the time of entry of Campylobacter and Salmonella into the brooder house, which is the first stage of commercial turkey production. In trial 1, birds (∼100 per time point) were monitored by conventional culture at three intervals (0, 9, and 16 days of age). Campylobacter spp. were not detected in poults at the day of hatch; Salmonella was isolated from the ceca (3.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…These data were supported by other studies showing that birds are not colonized at the time of eclosion and Campylobacter are rarely isolated from chicks younger than 14 d (Pokamunski et al, 1986;Gregory et al, 1997;Evans and Sayers, 2000;Hafez et al, 2001;Sahin et al, 2003;Wesley and Muraoka, 2011). During daily analysis of drinking water and feed samples, the first detection of Campylobacter DNA was successful in water at d 6 after restocking.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These data were supported by other studies showing that birds are not colonized at the time of eclosion and Campylobacter are rarely isolated from chicks younger than 14 d (Pokamunski et al, 1986;Gregory et al, 1997;Evans and Sayers, 2000;Hafez et al, 2001;Sahin et al, 2003;Wesley and Muraoka, 2011). During daily analysis of drinking water and feed samples, the first detection of Campylobacter DNA was successful in water at d 6 after restocking.…”
Section: Discussionsupporting
confidence: 76%
“…Consequently, it is of great importance to identify and assess the potential risks of infection along the production chain of turkey meat products (Atanassova et al, 2007). Previous studies showed that chicks were apparently not infected at the hatch, indicating that the young chicks became infected at the farm through the introduction of the organism via biotic and abiotic sources that may include drinking water, feed, litter, worker boots, wild animals, insects, and so on (Gregory et al, 1997;Wesley and Muraoka, 2011). In recent years, it has become evident that biofilms in drinking water pipe networks can become transient or long-term habitats for hygienically relevant microorganisms, including Campylobacter.…”
Section: Introductionmentioning
confidence: 99%
“…The normal vector of the plane XOY is: n=(0, 0, 1). The cosine of the projection angle of the egg surface is: (10) Although the function expression of z=f(x, y) was unknown, the coordinates of each point on the surface had been calculated, therefore we can use finite differences to calculate the partial derivatives:…”
Section: Figure 11 Calculation Of Actual Area For Egg Surfacementioning
confidence: 99%
“…During the process of production, storage and transportation, eggs may be polluted by blood from a prolapsed cloaca, faecal, water stains, grease, oil stains, etc [8] . Dirt stains may exist in different types of pathogenic bacteria, such as Salmonella, Escherichia coli and Staphylococcus, which may cause serious foodborne illness [9,10] . Moreover, cross-contamination may occur in the process of transportation and storage of eggs.…”
Section: Introduction mentioning
confidence: 99%
“…An egg may be considered clean if it has only very small specks, stains, or cage marks-if such specks, stains, or cage marks are not of sufficient number or intensity to detract from the generally clean appearance of the egg (United States Department of Agriculture 2000). When an egg presents organic residuals on the surface, such as blood, feces, and yolk, this could contaminate other eggs and this could have negative economic consequences (since when assigning a quality designation to an individual egg, freedom from stains, from foreign material, and the presence of discolorations on the shell are considered) and could cause sanitary problems (because different types of harmful bacteria, e.g., Salmonella, Enterobacter, and Staphylococcus, could be deposited along with the dirt on the outside of an egg and they could penetrate into the shell) (Mor-Mur and Yuste 2010; Wesley and Muraoka 2011). In Europe, market regulations do not allow any egg washing process, as it happens in the USA.…”
Section: Introductionmentioning
confidence: 99%